Shear Response of Fibrous High Strength Concrete Beams without Web Reinforcement - Sudheer Reddy, L.; Ramana Rao, N.V.; Gunneswara Rao, T.D. (Civil Engineering Dimension, 2011)
The use of steel fibers to improve the mechanical properties of concrete has been the ongoing interest in the research work. This paper deals with one such improvement in the mechanical property of concrete, which is the shear strength. In this paper an attempt has been made to study the improvement of shear strength of high strength concrete beams (70 MPa) with different shear span to depth ratios (a/d = 1, 2, 3, and 4) and various dosages of fibers (0.4%, 0.8%, and 1.2% by volume of concrete), without shear reinforcement. The experimental work revealed that steel fiber volume has different influence at different shear span to depth ratios (a/d). The test results indicated an increase in the cracking shear resistance noticeably and ultimate shear strength moderately.